Speaking is a key tool for development of learners productive skills (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
One of the most important factors in communicating with others is our nonverbal communication. We are aware and in control of the words that we speak, but often the nonverbal cues we send may go unnoticed. “We can reinforce, contradict, substitute, complement, or emphasize our verbal communication with non-verbal cues such as gestures, expressions and vocal inflection.” Nonverbal cues are so strong because they communicate to others on a subconscious level, causing individuals to regard nonverbal communication as “true” communication because it provides real cues and emotions. When verbal language and body language are congruent, this works to enhance the overall quality of the message and allow it to resonate with the individual receiving the message. On the opposite end of the spectrum, there can also be a sense of mistrust developed when body language does not match up to what is being verbalized. When there is a lack of congruence between verbal and nonverbal messages, this acts as a mental red flag to anybody receiving the message, and causes them to be on guard. Body language also works to display confidence and other desirable traits. In the case of a potential job opportunity, displaying confidence can be the driving factor in whether an employee gets hired or not. Likewise, as an employer, it is essential to let applicants know that you are confident in the company and work you do.